Retention of a Flowable Composite Resin in Comparison to a Conventional Resin-Based Sealant: One-year Follow-up - M. Jafarzadeh; B. Malekafzali; N. Tadayon; S. Fallahi (Tehran University of Medical Sciences, 2010)
Objective: Long-term retention of pit and fissure sealants is crucial for their success. This clinical study evaluated the retention rate of a flowable composite resin (Filtek Supreme XT Flowable Restorative) compared to a conventional resin-based sealant (Concise Light Cure White Sealant) over 12 months. Materials and Methods: Forty subjects aged 6 to 9 years were included in the study. Using a half-mouth design, a total of 80 first permanent molars were sealed with conventional fissure sealant on one side of the mouth and flowable composite on the contralateral side. Clinical evaluation was performed at 3, 6, and 12 months by a single blind examiner and the retention was classified as complete retention, partial loss, or total loss. Results: For both materials, there was no total loss of sealants over 12 months. Partial loss of both materials was observed in one sealant after 3 months. After 6 months, 36 teeth sealed with conventional fissure sealant were intact compared with 37 sealed with a flowable composite, and after 12 months, 33 teeth sealed with conventional fissure sealant were intact compared with 35 that were sealed with a flowable composite. There were no statistically significant difference (P>0.05) between the two materials regarding the retention rate at each follow-up period. Conclusion: As flowable composite resulted in comparable sealant retention rates, this material could be a good choice for fissure sealant.